Architecture for Internet of Things (IOT) for Home Automation (International Journal of Engineering and Computer Science, 2017)
Today’s, smart objects in Internet of Things (IOT) are able to detect their state and share it with other objects across the Internet, thus collaboratively making intelligent decisions on their own. Humans always find alternatives around them to carry out their work smoothly. Service provisioning in IOT should also be made capable of providing similar or alternate objects that are aligned with user requirements, current context and previous knowledge without any human intervention. With advancement of Automation technology, life is getting simpler and easier in all aspects. Now a day’s Automatic systems are being preferred over manual system. Traditional methods of household chores are replaced by automation system which is adaptable with the modern world. The manual systems are not more acceptable by the new generation peoples, so traditional methods are to be replaced. We have reported an effective implementation for Internet of Things used for monitoring regular domestic conditions by sensing system. Architecture of home automation is based on the appliances fault detection unit, kitchen safety unit, grocery monitoring unit. This smart object in Internet of Things (IOT) is able to detect their state and share it with other objects across the Internet, thus collaboratively making intelligent decisions on their own.